Application Repastra-G: Revolution Pasar Tradisional Gubeng Upaya Meningkatkan Daya Saing Globalisasi UMKM sebagai Peningkatan Ekonomi Sosial Ekonomi/UMKM - Damara Agasta, Dwi (Reinforce: Journal of Sharia Management, 2024)
In the digital age, technology utilization is commonplace in economic growth, but traditional markets seem to be lagging behind. Indonesia currently has approximately 13,450 traditional markets that accommodate around 13 million stall vendors and over 9 million street vendors. Instead of being a support, the rapid development of e-commerce and online shopping has become a major competitor, threatening the percentage of the economy that has been supported by this sector. The positive potential of technology for traditional markets is actually abundant. However, in reality, technology has become a threat to the sustainability of traditional markets and the MSMEs that operate under them. The author uses a literature review method, focusing on the role of digital technology in economic growth that is ready to compete with modern (online) markets. Therefore, the author developed a platform that can be used by both consumers and sellers, capable of revolutionizing the concept of sales in the Gadang Malang traditional market. The platform, named REPASTRA-G, combines digital technology with local cultural richness to create an ecosystem that benefits MSMEs and street vendors. This platform offers features such as Maps REPASTRA-G, Smart Pecagin, and Serc Kios, as well as promoting local products and showcasing the stories behind each product, to preserve local culture. REPASTRA-G demonstrates that technology can be the key to empowering MSMEs and street vendors, reviving traditional markets, and preserving local culture. With a smart and integrated approach, REPASTRA-G can serve as an example for other traditional markets in Indonesia, helping them compete in the digital age.